A review of the genus Corynoneura Winnertz (Diptera: Chironomidae) from the Neotropical region - Wiedenbrug, Sofia; Lamas, Carlos E.; Trivinho-Strixino, Susana (Zootaxa, 2012)
Currently the genus Corynoneura Winnertz comprises 10 species already cited or described for the Neotropical region. Inthe present paper 15 new species are described for the Neotropics: 12 new species are described from Brazil, five of themare described as male, female, pupa and larva, Corynoneura canchim sp. n., C. diogo sp. n., C. espraiado sp. n., C.humbertoi sp. n., C. salviniatilis sp. n.; three as male, pupa and larva, C. franciscoi sp. n.; C. longiantenna sp. n. and C.renata sp. n.; the species C. sisbiota sp. n. as male, female and pupa; C. bodoquena sp. n. as male and pupa and C. boraceiasp. n. and C. vidiapodeme sp. n. as males. Corynoneura trondi sp. n. is described from Chile (male, pupa), C. guanacastesp. n. from Costa Rica (male) and C. zempoala sp. n. from Mexico (male). The knowledge of the distribution ofCorynoneura fortispicula, C. sertaodaquina, C. septadentata and C. unicapsulata all species described by Wiedenbrugand Trivinho-Strixino (2011) as well as Corynoneura ferelobata Sublette et Sasa is extended. A larval morphotype is also included. Keys for males, females, pupae and larvae to known species of the Neotropical Corynoneura are given.